Detection of biocolloids in aquatic media by Nano-Particle Analyzer. Issue 1 (2005) - Bundschuh Bundschuh, T. T.; Wagner Wagner, T. T.; Eberhagen Eberhagen, I. I.; Hambsch Hambsch, B. B.; KÖster KÖster, R. R.
Abstract : The Nano-Particle Analyzer (NPA) based on Laser-Induced Breakdown Detection (LIBD) selectively generates and detects plasma events on colloids in aquatic media. Here, it is made use of the fact that the power density required for plasma generation decreases from the gaseous to the solid medium. At an adequate laser pulse energy, plasmas can thus be generated selectively on colloids. The detections of biocolloids by LIBD-based NPA as described in this paper for the first time clearly reveal that the method is well suited for detecting not only non-biological particulate matter in water, but also microorganisms in the transition range between solid and liquid matter. Consequently, the method can be used for online-monitoring, for example of both the non-biological and biological particulate content during the purification, transport and storage of drinking water. It is further possible to monitor online contamination of pure water or process chemicals by biological matter e.g. in biomedical industry.